Serat Centhini: Ajaran Menjadi Manusia Sejati: Serat Centhini: Teachings on How to Become a True Human Being - Alfariz, Fitri (Jurnal Filsafat Indonesia, 2025)
Human research is always interesting to be discussed and researched because humans have always been a mystery for themselves as well as for others. People today can experience chaos if the strong flow of globalization, technology, and sharper information is not coupled with the understanding of a good self-concept. People can learn the concepts of self from various sources, one of them is Serat Centhini. This method of research is the research of libraries with the main manuscript of the Serat Centhini by Elizabeth D. Inandiak and supported by live interviews. The results of this study stated that the perfect human concept in Serat Centhini is to be a man who means that human beings must always strive for salvation, happiness, and the welfare of living in a world that is a small meaningful world Personal and family, a great world that means society, nation, country, and the eternal world that means natural afterlife, the concept of man in Serat Centhini leads to the flow of philosophy of human dualism which means humans live in two worlds: the World Materials and the spiritual world.